Airbag fabric with improved seam performance

Polyamide fabrics with high RV and edge comb resistance address seam combing issues in airbags, enhancing stability and resistance to hot gas flow, ensuring robustness and compactness without additional weight or cost.

JP2025502372APending Publication Date: 2025-01-24INVISTA TEXTILES (U K) LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024542332
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-28
Filing Date
2023-01-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Airbag cushions face challenges in maintaining mechanical robustness and heat resistance under high temperatures and pressures, particularly at seams where seam combing occurs, leading to uncontrolled gas leakage and potential structure rupture, without compromising compactness and stowability.

Method used

The use of polyamide fabrics with a relative viscosity (RV) of 90 or more, edge comb resistance of at least 500N in both warp and weft directions, and dynamic air permeability of 500 mm/s or less, which are woven to improve seam performance.

Benefits of technology

The solution enhances seam stability and resistance to hot gas flow, reducing seam opening area and maintaining fabric integrity under thermal and mechanical stress, while maintaining low weight and packability, thus improving airbag performance without increasing material complexity or cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502372000002
    Figure 2025502372000002
  • Figure 2025502372000001
    Figure 2025502372000001
  • Figure 2025502372000003
    Figure 2025502372000003
Patent Text Reader

Abstract

1. A woven fabric formed from polyamide fibers, wherein: a. the woven fabric exhibits a fabric relative viscosity of 90 or greater; b. the fabric has an edge comb resistance of at least 500 N in each of the warp and weft directions; and c. the fabric has a dynamic air permeability of 500 mm / sec or less, and the fabric exhibits improved seam performance upon deployment compared to a control fabric having the same fabric construction characterized by a fabric RV of greater than 90.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to woven fabrics suitable for airbags, the use of such woven fabrics to improve airbag properties, methods of making the airbag fabrics, and the airbags themselves.The present invention further relates to a suture. [Background technology]

[0002] In frontal airbag cushions (driver and passenger), there is a continuing trend for hotter and smaller inflators in the airbag module. Such higher power inflators mean that the airbag cushion needs to be more robust in maintaining performance under the higher temperatures and higher pressures experienced during deployment. Additionally, there is a trend to minimize the size and weight of the interior components of the automobile to optimize efficiency. At the same time, changing crash test requirements are causing the cushions to become larger, which makes good packability more difficult to achieve and further increases stresses on the cushion. Thus, there is a need for airbag cushion modules to maintain robustness under high temperatures and pressures at favorable costs and without compromising the packability or compactness of the airbag. Correspondingly, it is desirable to improve the mechanical integrity and heat resistance of the airbag cushion in the airbag module without requiring additional materials such as the use of heavier fabrics or reinforcing materials. With respect to frontal airbags, the need for improved mechanical robustness and heat resistant fabrics is particularly acute.

[0003] A major issue for airbag designers is the performance of airbag cushions at seams, where the heated pressurized gas created during deployment can create high stress areas in small sections of the fabric along the seams. This is primarily due to the presence of stitching threads along the seams. This results in warp and weft threads moving relative to each other, causing localized stretching of the threads in the fabric. This leads to the enlargement of stitching holes, resulting in a phenomenon known as "seam combing." Since frontal airbags are typically filled with hot gas, the presence of small holes in an otherwise very low porosity structure can lead to preferential flow of hot gas through the holes, which can cause softening of the threads, reduced tensile modulus, and increased elongation for a comparable load. Thus, seam combing is an increasingly critical failure mode of airbag cushions as the inflators in the airbag modules become more and more powerful. This creates a favorable path for hot gas to escape from the inflation, which can lead to unacceptable cushion performance due to uncontrolled gas leakage, a condition that can lead to melting and rupture of the structure, a particularly severe event. There is great value in overcoming this problem in a manner that does not compromise the "compactness" of the airbag cushion.

[0004] Traditionally, the seam combing effect of airbag cushions can be improved by using fabrics with increased weight or density or higher structure, by using silicone coatings, and by using alternative reinforcements such as seam tapes, seam sealants, or heat shields. However, all of these approaches have a negative impact on the complexity, cost, and packability of the airbag cushion. Thus, there remains a need to further improve the mechanical robustness and heat resistance of fabrics without compromising an optimized balance of cost, complexity, and packability of the airbag cushion.

[0005] WO 2021193966(A1) and EP 2264235(B1) describe how improvements can be made to seam slip behavior in airbags by weaving high tenacity polyamide fibers into a dense fabric with high edge comb resistance. The relationship between fabric RV and improved seam fastness of the fabric is not disclosed. In reference EP 3674458, which discloses lightweight airbag fabrics with improved fastness, it is reported that the use of fibers with a sulfuric acid relative viscosity (RV) of more than 3.5 causes reduced cost efficiency, challenges in fiber drawing, and leads to problems in achieving the required fiber strength. For context, a sulfuric acid RV of 3.5 is converted to a formic acid RV of 95. According to this reference, fibers with a sulfate RV of more than 3.5 would not be suitable for yarn production for airbag fibers.

[0006] It is an object of the present invention to address the problems discussed above, and in particular to provide improved woven fabrics and airbags made from the fabrics that exhibit greater mechanical robustness and heat resistance during deployment without compromising an optimized balance of airbag cost, complexity and packability. Summary of the Invention

[0007] The problem of poor seam performance, specifically seam combing, where seams have a higher tendency to open under high heat (thermal load) and pressure (mechanical stress), is solved by the use of polyamide fabrics with high fabric RV, which provides resistance to hot gas flow. The problem of poor seam performance was previously addressed by using fabrics with high structure. However, the inventors have found that by increasing the RV of the polyamide, improved seam performance can be achieved, which is particularly useful in fabrics with lighter structure. This benefit is particularly evident when the dynamic air permeability is less than 500 mm / s and when the edge comb resistance of the fabric is greater than 500 N. The concept of using higher RV fibers to improve the resistance of fabrics to melting due to contact with hot metal particles has been explored in the past, but the effect of RV on seam performance has not been described.

[0008] The term "fabric RV" as used herein specifically applies to the measurement of RV on fibers extracted from a fabric, rather than fiber samples collected at the spinning process. Traditionally, fiber RV refers to the RV of fibers collected from below the spinneret, before they are drawn on the godets on the spinning machine. Fiber RV is known to decrease significantly going from free-fall yarn to drawn yarn in the final fabric, the extent of which depends on the process involved in making the fiber and fabric. In the present invention, "fabric RV" is defined as formic acid relative viscosity, measured as described herein below.

[0009] According to a first aspect of the invention there is provided a woven fabric formed from polyamide fibres, comprising: a. The woven fabric exhibits a fabric relative viscosity (fabric RV) of 90 or greater; b. the edge comb resistance of the fabric is at least 500 N in each of the warp and weft directions; c. The fabric has a dynamic air permeability of 500 mm / sec or less; A fabric, as defined herein, is provided that exhibits improved seam performance upon deployment as compared to a control fabric having the same fabric construction characterized by a fabric RV of greater than 90 as measured by a Hot Air Seam Combing Test.

[0010] Thus, the inventors have found that the mechanical robustness and heat resistance of airbag fabrics at seams can be improved by the use of polyamide fabrics with high fabric RV, which is facilitated by the use of higher molecular weight or higher relative viscosity (RV) polyamide fibers in the fabric. Specifically, improved deformation resistance or reduced elongation aspects at seam locations of fabrics and fibers are observed when fabrics with a relative viscosity (RV) of at least 90 are used. Preferentially, the seam combing effect is significantly reduced by the use of fabrics with fabric RV≧100, preferably the fabric RV is greater than 100. Preferably, the fabric RV is in the range of 90-200, more preferably 90-150, more preferably 90-130. Preferably, the fabric RV is in the range of 100-200, more preferably 100-150, more preferably 100-130. Preferably, in each of the above ranges, the fabric RV is greater than 100. [Brief description of the drawings]

[0011] (No corresponding description in the brief description of the drawings) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The woven fabric of the present invention is composed of high tenacity spun synthetic polyamide yarns. The yarns are made from fibers in the form of continuous filaments. Such filaments are formed by extruding molten polymer at high temperature and pressure through a spinneret, which is subsequently quenched in air, coated with a spin-finish lubricant, drawn between a pair of godets, lightly textured to provide sufficient entanglement to create a coherent yarn, and then wound into bobbins onto a cardboard tube.

[0013] The spin finish on the filaments facilitates processing of the yarn during its manufacture and may subsequently be removed to provide the finished woven fabric, depending on the requirements of subsequent processing. Removal of the spin finish may be performed before, during or after weaving (preferably during or after weaving) according to conventional techniques known in the art. In the woven fabric of the present invention, the polyamide is or comprises at least one polyamide selected from nylon 6,6 (PA-6,6), nylon 6 (PA-6), nylon 7 (PA-7), nylon 4,6 (PA-4,6), nylon 4,10 (PA-4,10), nylon 5,6 (PA-5,6), nylon 5,10 (PA-5,10), nylon 6,10 (PA-6,10), nylon 12 (PA-12) and nylon 6,12 (PA-6,12). When more than one polyamide is present, the polyamide may be a copolymer or blend of such polyamides. In a preferred, but non-limiting embodiment, the polyamide is nylon 6,6.

[0014] At least a majority (preferably all) of the yarns used in the warp direction of the fabric are preferably formed from synthetic fibers made from a single polyamide composition. Similarly, at least a majority (preferably all) of the yarns used in the weft direction of the fabric are preferably formed from synthetic fibers made from a single polyamide composition. In a preferred, but non-limiting embodiment, at least a majority (preferably all) of the yarns used in the warp and weft directions of the fabric are formed from synthetic fibers made from a single polyamide composition. Preferably, a single polyamide is used in each of the warp and weft directions, and preferably the same polyamide is used in both the warp and weft directions.

[0015] Polyamides can be produced by conventional means known in the art. Polyamides can be produced from intermediates produced via biosynthetic routes or via conventional petrochemical routes. The relative viscosity of polyamides can be increased by increasing the degree of polymerization, i.e., molecular weight, of the polyamide, as known in the art. For example, the molecular weight and relative viscosity can be increased by a solid-state polymerization process, typically carried out at elevated temperatures (e.g., about 180° C.) under dry nitrogen.

[0016] In the woven fabric of the present invention, at least a majority (preferably all) of the yarns in the warp direction are yarns having a tenacity of 6.0 to 10.0 cN / dtex. Similarly, at least a majority (preferably all) of the yarns in the weft direction are yarns having a tenacity of 6.0 to 10.0 cN / dtex. In a preferred, but non-limiting embodiment, at least a majority (preferably all) of the yarns in the warp and weft directions are yarns having a tenacity of 6.0 to 10.0 cN / dtex.

[0017] The yarn used in the present invention preferably has a linear mass density in the range of about 100 to about 2000 decitex, preferably about 150 to about 1000 decitex, preferably about 150 to about 940 decitex, preferably about 150 to about 750 decitex, preferably more than 250 to about 750 decitex, preferably about 300 to about 750 decitex, preferably about 350 to about 750 decitex.

[0018] The linear mass density of the fibers making up the yarn is preferably within the range of about 1 to about 25 decitex per filament (DPF), or about 2 to about 12 decitex per filament (DPF).

[0019] The woven fabric of the present invention is preferably made from yarns having at least 14.0 ends / cm, preferably 14.0-30.0 ends / cm, preferably 14.0-24.0 ends / cm, preferably 16.0-24.0 ends / cm, preferably 22.5 ends / cm or less, preferably 21.0 ends / cm or less, preferably 16.0-22.5 ends / cm, preferably 16.0-21.0 ends / cm. Preferably, the woven fabric exhibits a symmetrical structure. Thus, the ends / cm of the warp yarns are preferably the same as the ends / cm of the weft yarns.

[0020] The woven fabric of the present invention may be formed from warp and weft yarns using weaving techniques known in the art. Suitable weaving techniques include, but are not limited to, plain weave, twill weave, satin weave, modified weaves of these types, or multiaxial weave. Preferably, the weave is a plain weave. Suitable looms that can be used for weaving include water jet looms, air jet looms, or rapier looms, and preferably the loom is a water jet loom. The fabric may be finished according to any method known in the art, including on-loom drying, scouring, can drying, and heat setting. Preferably, the woven fabric is a heat set woven fabric. Thus, preferably, the method of the present invention includes a heat setting step after weaving and scouring to provide the final finished fabric.

[0021] After finishing, the woven fabric is preferably used to manufacture articles from the woven fabric without further processing. In particular, the woven fabric is preferably not exposed to high temperatures and pressures, for example, by calendaring and / or in a manner that would permanently modify the cross-section and fuse some or all of the fibers in the yarn onto the upper and / or lower surfaces.

[0022] The woven fabric preferably has a fiber count of 130 to 500 g / m 2 , preferably 300 g / m 2 Preferably, 260 g / m or less 2 Preferably, 250 g / m or less 2Preferably, 225 g / m or less 2 Preferably, 220 g / m or less 2 or less, preferably at least about 140 g / m 2 , preferably at least about 150 g / m 2 , preferably at least about 160 g / m 2 , typically at least 180 g / m 2 In a preferred embodiment, the woven fabric of the present invention has a total fabric weight of 160 to 260 g / m 2 , preferably 170 to 225 g / m 2 , preferably 170 to 220 g / m 2 The total fabric weight is

[0023] The total thickness of the woven fabric is preferably 0.40 mm or less, preferably 0.35 mm or less, and preferably at least 0.16 mm, typically at least 0.22 mm, typically at least 0.26 mm, typically at least 0.29 mm, and typically at least 0.30 mm. Preferably, the total fabric thickness is 0.28-0.40 mm, preferably 0.29-0.40 mm, preferably 0.30-0.35 mm.

[0024] The woven fabric of the present invention preferably has a strength of 750 kg / m 3 Less than or equal to 725 kg / m 3 Typically, 700 kg / m 3 It has the following bulk density:

[0025] The woven fabric exhibits a dynamic air permeability (DAP) of 500 or less, preferably 450 or less, preferably 400 or less, preferably 300 or less, preferably 200 mm / sec or less, when the fabric is unaged.

[0026] The fabric preferably has a viscosity of 4.0 or less, preferably 3.0 or less, preferably 2.5 or less, preferably 2.0 l / dm when the fabric is unaged. 2 / min or less.

[0027] Edgecomb resistance is a measure of the relative tendency of a fabric to pull apart under seam stress. Maintaining good edgecomb resistance is important to ensure that the fabric remains stable against relative movement between the warp and weft threadlines and the seams before or during hot gas deployment. The woven fabric of the present invention exhibits an edgecomb resistance of at least 500N, preferably at least 600N, preferably at least 700N, and preferably at least 800N in each of the warp and weft directions.

[0028] The stiffness of a fabric is an important measure of the fabric's ability to conform to and deploy from an airbag module. The fabric should preferably exhibit a relatively low stiffness to improve packing efficiency and facilitate smooth deployment, but at least exhibit low stiffness while maintaining high edge comb resistance. Various properties of the yarns, including decitex, decitex per filament, fabric weight, construction, and thickness, affect the stiffness of the fabric. The stiffness of a woven fabric is also altered by heat setting, which is conventionally performed during fabric manufacture to provide a final finished woven fabric for forming an airbag or other article. Specifically, heat setting typically increases the stiffness of the fabric. The stiffness of the woven fabric of the present invention should be 38.0 N or less, preferably 35.0 N or less, preferably 30.0 N or less, preferably 28.0 N or less, preferably 25.0 N or less, in each of the warp and weft directions.

[0029] The cloth cover factor of a fabric is a number indicating how much of the fabric area is covered by the constituent yarns. The cloth cover factor of the fabric of the present invention is preferably at least 78, preferably at least 85, preferably at least 90. Typically, the cloth cover factor is 100 or less. To provide a lightweight fabric with surprisingly good seam performance and advantageously low stiffness, the cloth cover factor is preferably 97 or less, preferably 95 or less, and an advantageous balance of low stiffness and good seam performance can be achieved with a cloth cover factor of 92 or less while retaining an acceptably low permeability. Preferably, the cloth cover factor is in the range of 78 to 97, preferably 85 to 97, preferably 85 to 95, or 85 to 92.

[0030] Preferably, the tear strength of the fabric in each of the warp and weft directions is at least 120N, preferably at least 140N, preferably at least 150N, preferably at least 170N, when the fabric is unaged.

[0031] The tensile breaking force (also referred to herein as maximum force) of the woven fabric in each of the warp and weft directions is preferably at least 3000 N, preferably at least 3200 N, preferably at least 3500 N, when the fabric is unaged.

[0032] The tensile elongation at maximum force of the woven fabric in each of the warp and weft directions is preferably at least 20%, preferably at least 25%, preferably at least 28%, preferably at least 30%, when the fabric is unaged.

[0033] The woven fabric of the present invention preferably has a seam open area (or seam combing index) of ≦0.20 mm when measured by the Hot Air Seam Combing Test described herein. 2 / stitch, preferably ≦0.18mm 2 / stitch, preferably ≦0.16mm2 / stitch, preferably ≦0.15mm 2 / stitch, preferably ≦0.10mm 2 / Presents stitches.

[0034] The woven fabrics of the present invention are preferably uncoated to further the goals of reduced weight and improved packability, and to minimize material costs and environmental impacts through polymer recycling.Fabrics that include layers or coatings to reduce air permeability are commonly used in airbags.

[0035] However, a further non-limiting embodiment is that the fabric of the present invention is "coated" so that further improvements can be made to the permeability or resistance of the fabric to hot particulates and gases from the inflator. Woven fabrics containing an additional layer or coating are referred to herein as "coated woven fabrics", where the "coating" takes the form of any coating, web, net, laminate or film that may be used, for example, to provide reduced air permeability or improved heat resistance. Examples of such coatings include polychloroprene, silicone-based coatings, polydimethylene siloxane, polyurethane and rubber compositions. Examples of such webs, nets and films include polyurethanes, polyacrylates, polyamides, polyesters, polyolefins, polyolefin elastomers and blends and copolymers thereof. It will be understood that the preferred uncoated woven fabrics of the present invention are not "coated woven fabrics" as defined herein.

[0036] The woven fabric of the present invention is particularly useful as an airbag fabric. The woven fabric may also be used to make articles selected from canvas, inflatable slides, temporary shelters, tents, ducts, covers, and print media. As used herein, the term "airbag" includes airbag cushions. Airbag cushions are typically formed from multiple panels of fabric and can be rapidly inflated. The woven fabrics described herein are preferably used in airbags sewn from multiple pieces of fabric. For this reason, airbags of particular interest in the present invention are airbags other than one piece woven (OPW) airbags. The present invention is applicable to frontal, knee, distal, side / thorax, and side curtain airbags, but is particularly useful in frontal airbags such as driver and passenger airbags where the thermal and mechanical loads are very high and the airbags tend not to be coated.

[0037] According to a second aspect of the present invention there is provided a woven fabric formed from polyamide fibres, a. The woven fabric exhibits a fabric relative viscosity (fabric RV) of 90 or greater; b. the edge comb resistance of the fabric is at least 500 N in each of the warp and weft directions; c. The fabric has a dynamic air permeability of 500 mm / sec or less; The fabric has a seam open area of ​​≦0.20 mm when measured by the Hot Air Seam Combing Test described herein. 2 / stitch, preferably ≦0.18mm 2 / stitch, preferably ≦0.16mm 2 / stitch, preferably ≦0.15mm 2 / stitch, preferably ≦0.10mm 2 / Shows stitches.

[0038] According to a third aspect of the present invention there is provided an article, preferably an airbag, made from the fabric of the first or second aspect.

[0039] According to a fourth aspect of the present invention there is provided the use of a fabric according to the first or second aspect as an airbag fabric for the purposes of improving the seam performance of an airbag during deployment. With respect to the fabric according to the second aspect the improvement may be achieved by providing the fabric with a seam open area of ​​≦0.20 mm, as defined above. 2 / stitch, preferably ≦0.18mm 2 / stitch, preferably ≦0.16mm 2 For fabrics according to the first aspect, the improvement is evaluated in comparison to a control fabric having the same fabric construction and characterized by a fabric RV of <90. The improvement in seam open area and seam performance is measured by the Hot Air Seam Combing Test defined herein.

[0040] According to a fifth aspect of the present invention there is provided a method of improving seam performance of an airbag during deployment, the method comprising fabricating an airbag from a woven textile according to the first or second aspect. For textiles according to the second aspect the improvement may be achieved by providing an airbag with a seam open area of ​​≦0.20 mm, as defined above. 2 / stitch, preferably ≦0.18mm 2 / stitch, preferably ≦0.16mm 2 For fabrics according to the first aspect, the improvement is evaluated in comparison to a control fabric having the same fabric construction and characterized by a fabric RV of <90. The improvement in seam open area and seam performance is measured by the Hot Air Seam Combing Test defined herein.

[0041] According to a sixth aspect of the invention there is provided a suture formed by twisting polyamide fibres, the fibres extracted from the yarn exhibiting an RV > 90. The suture may be used to impart improved robustness to seams, particularly airbag seams. It will be appreciated that the RV of the fibres extracted from the yarn according to the sixth aspect of the invention is measured in accordance with the fabric RV test described herein.

[0042] It will be understood that the disclosures and preferences discussed herein with respect to the first aspect of the invention apply equally to all other aspects of the invention.

[0043] The following test methods were used to characterize the woven fabrics disclosed herein.

[0044] Test Method Fabric Relative Viscosity (RV) Fabric RV specifically applies to the measurement of RV on fibers extracted from fabrics, rather than fiber samples collected at the spinning process. As used herein, the term "fabric RV" refers to RV measured by the following test: Relative Viscosity (RV) is measured on fabrics according to ASTM D789-19 (2019) using a 90% formic acid solution. One 20g fabric sample is required for each iteration of this analysis. Prior to RV measurement, each sample is treated to remove residual fiber lubricants, also known as spin finishes. To remove the lubricants, each sample of fabric is immersed in enough methylene chloride to completely cover the sample. The sample is allowed to soak for 20 minutes with stirring in a covered extraction funnel. This procedure is then repeated. Once the second methylene chloride wash is complete, the fabric is immersed in enough 1:1 methanol:methylene chloride to completely cover the sample. The sample is allowed to soak for 20 minutes with stirring in a covered extraction funnel. This procedure is repeated two more times. Once all five dipping steps are complete, the remaining solvent is blown off the fabric sample with clean pressurized air. The fabric is then allowed to air dry thoroughly in an exhaust hood. Once dry, the relative viscosity of the fabric sample is measured according to ASTM D789-19.

[0045] Dynamic Air Permeability (DAP) Dynamic air permeability is defined as the average velocity (mm / sec) of air or gas within a selected test pressure range of 30 to 70 kPa, converted to a pressure of 100 kPa (14.2 psi) and a temperature of 20°C. Another parameter, the curve index E (of the air permeability curve), is also measured automatically during the dynamic air permeability test, but it has no units. Dynamic air permeability is tested according to test standard ASTM D6476-12(2021), but with the following modifications: The limits of the measured pressure range (as set on the test apparatus) are 30 to 70 kPa. The starting pressure (as set on the test fixture) is adjusted to achieve a peak pressure of 100 + / - 5 kPa. The test head volume should not exceed 400 cm unless the specified starting pressure can be achieved with this head. 3 where other interchangeable test heads (volumes 100, 200, 800 and 1600 cm) may be used as found appropriate for the fabric under test. 3 ) should be used. The Dynamic Air Permeability Test is conducted at six sites on the test fabric in a sampling pattern across and along the fabric to test six separate areas of warp and weft yarn lines within the fabric. The reported dynamic air permeability results are the average of six DAP measurements in mm / sec.

[0046] Static Air Permeability (SAP) Static air permeability (l / dm 2 The rotational speed (units: rotational speed / minute) is tested according to test standard ISO 9237 (1995), but with the modifications listed below. The test area is 100 cm 2 It is. The test pressure (partial vacuum) is 500 Pa. Each individual test value is corrected for edge leakage. The Static Air Permeability Test is conducted at six sites on the test fabric in a sampling pattern across and along the fabric to test six separate areas of warp and weft yarn lines within the fabric. Static air permeability results reported are in l / dm 2 The average of six corrected measurements is taken in units of / min.

[0047] Fabric Tensile Test The maximum force (N) and the elongation at maximum force (%) are tested according to the standard ISO 13934-1 (2013), but with the modifications as listed below. The initial gauge (clamp) length set on the Instron tensile tester is 200 mm. The crosshead speed on the Instron is set at 200 mm / min. The fabric samples are first cut to size 350 x 60 mm, but are then frayed by unraveling the thread lines on the long sides to a test width of 50 mm. Tensile tests are performed on five warp direction and five weft direction specimens cut from each test fabric in a diagonal cross pattern, avoiding any area within 200 mm of the fabric selvedge. The reported results for maximum force (also known as breaking force or breaking load) are the average of the maximum force results of five warp direction specimens and five (separate) weft direction specimens tested in Newtons (N). The reported results for elongation at maximum force (also known as elongation or stretch) are the average (%) of the elongation at maximum force results of five warp direction samples and five (separate) weft direction samples tested.

[0048] Tear force Tear force (also known as tear strength) is measured in Newtons (N) and is tested according to standard ISO 13937-2 (2000), but with the modifications listed below. The size of the fabric sample was 150 mm x 200 mm (100 mm slit extending from the midpoint of the narrow end to the center). Tear tests are performed on five warp direction and five weft direction specimens cut from each test fabric in a diagonal cross pattern, avoiding any area within 200 mm of the fabric selvedge. Warp direction tear results are taken from samples tested where the tear is longitudinal (i.e., the warp thread line tears), while weft direction results are taken from samples tested where the tear is transverse (i.e., the weft thread line tears). Each leg of the sample is folded in half and secured in Instron clamp grips according to Annex D / D.2 of ISO 13937-2. The evaluation of the test results shall be in accordance with Section 10.2 "Calculation using electronic devices" of ISO13937-2.

[0049] The reported results for the longitudinal tear force are the average of the tear force results of the five warp direction specimens in Newtons (N), while for the transverse tear force they are the average of the tear force results of the five weft direction specimens.

[0050] Edge Comb Resistor Edge comb resistance (also known as the edge pullout test) is measured in Newtons (N) and is tested according to standard ASTM D6479-15(2020), but with the modifications listed below. The edge distance was 5 mm, which is the distance between the end of the test specimen (positioned on a narrow protrusion machined in the test specimen holder during the test) and the line of the pin that performs the "pulling", i.e. this is the length of the thread line section that is pulled out during the test. Edgecomb resistance tests are performed on five warp direction and five weft direction specimens cut from each test fabric in a diagonal cross pattern, avoiding any area within 200 mm of the fabric selvedge.

[0051] Warp direction edgecomb resistance results are taken from test specimens having their major dimension parallel to the warp yarns, while weft direction results are taken from test specimens whose major dimension is parallel to the weft yarns.

[0052] The reported results for warp edge comb resistance are the average of the edge comb resistance results of five warp direction samples in Newtons (N), while for weft edge resistance they are the average of the results of five weft direction samples.

[0053] rigidity The stiffness in Newtons (N) of a fabric (also referred to herein as "King stiffness") is measured by a circular bending procedure and tested using a JA King pneumatic stiffness tester according to standard ASTM D4032-08 (2016), but with the modifications listed below. The plunger stroke speed is 2000 mm / min. Stiffness testing is performed on five warp direction and five weft direction specimens cut from each test fabric in a diagonal cross pattern, avoiding any area within 200 mm of the fabric selvedge. Each 200 x 100 mm specimen is folded once across its narrow dimension before being positioned on the instrument test platform for testing. The reported results for warp stiffness (in Newtons) are the average of the stiffness results of the five warp direction specimens, while the results for weft stiffness are the average of the five weft direction samples.

[0054] Warp direction stiffness results are taken from samples tested whose longest dimension (200mm) is parallel to the fabric warp direction, while weft direction results are taken from samples tested whose longest dimension (200mm) is parallel to the fabric weft direction.

[0055] Number or composition of fabrics Evaluated using ISO-7211-2 (1984). Fabric construction is determined as warp ends / cm and weft ends or picks / cm.

[0056] Fabric thickness Thickness tests are performed on fabric samples according to ISO 5084 (1996) conditioned to reference laboratory conditions of 20±2°C and 65±4% RH for at least 24 hours. Samples are cut from the fabric such that no two samples have common warp or weft threads. Samples are not cut within 20 cm of either selvedge or on any wrinkled, obviously damaged, or soiled fabric area. Samples are suitably cut using a cutter die with a hydraulic press. The thickness of five samples was measured with an electronic micrometer with a test range of 0-25 mm x 0.001 mm (with jaw faces of 6.5 mm diameter) and the results recorded. The reported results (in mm) are the average of the results of five individual samples.

[0057] Fabric Weight Fabric weight was measured according to ISO 3801 (1977) with EASC modifications and according to EASC instruction 99040180 covering fabric testing (sections 3.05 and 4.01). Weight tests are performed on samples of fabric conditioned to reference laboratory conditions of 20±2°C and 65±4% RH for at least 24 hours. Five square specimens measuring 10×10 cm are cut from the sample in a diagonal pattern across the fabric (each oriented at a 45° bias to the warp direction) such that no two specimens have warp or weft threads in common. No specimens are cut within 10 cm of either selvedge or on any creased, obviously damaged, or soiled fabric areas. A 10×10 cm cutter die with a hydraulic press is used to cut the specimens. Once cut, the five specimens are weighed on a 3-decimal balance in grams and the results recorded. Each result is multiplied by 100 to obtain a weight of g / m 2 The reported fabric weight result is the average of the five results.

[0058] Cover Factor Calculation The fabric cover factor is calculated according to the following formula: (Warp Ends / cm * √(dtex / 100))+(weft picks / cm * √(decitex / 100)

[0059] fabric bulk density The bulk density of a fabric is the weight of the fabric per unit area (g / m 2 ) divided by the fabric thickness measurement (mm), kg / m 3 is converted to units of

[0060] Seam Opening Area The seam performance of the fabrics was evaluated by measuring the seam open area by the Hot Air Seam Combing Test Method, which simulates the conditions during the deployment of a woven airbag. The test is designed to examine the seams of woven fabrics as they are heated under load.

[0061] Two woven fabrics with aligned warp and weft threads are overlapped and a single seam is stitched with a lockstitch pattern (5 stitches / cm) 19 mm from the cut edge. Using a 2800 dtex PTFE coated glass suture (e.g., Fil-tec BC24 Glass Lube 2lb, part no. 11031), only high temperature fabric deformation could be observed.

[0062] While the sewn fabrics are on top of each other, a template is placed against the cut edge of the sewn fabric and test strips are marked and cut according to the following dimensions: starting from the cut edge, 59 mm long (warp direction) and 75 mm wide, the width of the strip then tapers off from 75 mm to 50 mm over the next 10 mm length, and finally the width of the strip is 50 mm for the final 150 mm length (see Figure 1). The cut fabric is then unfolded.

[0063] The upper end of the sewn strip is clamped to a fixed beam and a load of 46 kg is applied to the lower end, which corresponds to a filament yarn stress of approximately 10 cN / tex (corresponding to the yarn stress in a typical woven fabric airbag at maximum airbag inflation pressure). A Milwaukee Tool Variable Temperature Corded Heat Gun Model # 8988-20 with a spreader nozzle at an operating temperature of 532°C is rotated to align the nozzle tip 32 mm away from the seam, with the air flow at 90° to the plane of the fabric and with the opposite side of the fabric not exposed to the hot air. The seam is stretched in this manner for 29.3 m. 3 The fabric is heated with a volumetric air flow rate of 100 rpm for 20 seconds, at which point the hot air gun is rotated away from the seam and the fabric is allowed to cool to room temperature.

[0064] Five fabric samples are tested and measured for repeatability as follows. The final result is the average of the results of the five samples. The fabric samples are conditioned at 20°C±2°C with a relative humidity of 65%±4% for 24 hours prior to testing according to ISO139:2005(E). The cooled sample is then backlit with an LED light source located approximately 2 cm behind the sample. While the cooled sample is under tension created by the tension weight, the seam area is photographed using a Dino-lite digital microscope to provide a photographic image with sufficient resolution to allow for a measurement accuracy of ±1 mm (preferably the photographic image is enlarged to a size of 21 cm×28 cm). The image is then inspected for visible openings in the seam (combing). Visible openings are defined as openings seen between the stitch and the next thread line of the stretched fiber in the seam. The image area (magnification = 23x ± 0.5x) covers a minimum of 9 consecutive stitches (centered on the middle 37.5 mm of the stitched sample, with the total width of the stitched sample being 75 mm) to provide sufficient reproducibility between samples. Measurements of these visible openings are made by marking the opening area with a trapezoidal element using image analysis software. The sum of the areas of these trapezoids gives the total stitch area of ​​the sample, which is then divided by the number of stitches evaluated to provide the seam combing area / stitch of the sample. The microscope reference scale is in mm (as these dimensions are preferably taken from magnified images). 2 This metric is used to calculate the true dimension of the seam open area in units of 1 / 2. This metric is defined as "seam open area" (also referred to as "seam combing index"). Optionally, image analysis software can calculate the seam open area automatically.

[0065] The present invention is further illustrated by the following examples. It will be understood that the examples are for illustrative purposes and are not intended to limit the invention as described above. Modifications of detail may be made without departing from the scope of the invention. EXAMPLES

[0066] A series of woven fabrics were prepared according to the above description using conventional methods. The woven fabrics had the properties shown in Table 1, measured as defined herein.

[0067] [Table 1]

[0068] Surprisingly, it has been observed that the seam open area after exposure to thermal and mechanical loads in the hot air seam combing test is significantly lower for the high fabric RV samples of the inventive examples 1 and 2 compared to the conventional fabrics with relatively low fabric RV of comparative examples 1-3, without compromising the mechanical properties of the fabric. Furthermore, the seam open area of ​​the inventive examples is comparable to that of comparative example 4, which has a much higher fabric structure and weight. Thus, the present invention surprisingly allows for superior seam fastness without the need to increase the fabric structure and weight.

[0069] Additionally, the woven fabrics of the present invention allow for a reduction in fabric stiffness which, combined with reduced fabric weight and thickness, translates into improved packability relative to fabrics with higher structure and weight while retaining acceptably low air permeability.

[0070] Thus, the woven fabrics of the present invention having high fabric RV surprisingly provide a combination of excellent seam performance, low stiffness and thickness (hence improved packability), excellent mechanical properties, and low air permeability not exhibited by any of the conventional fabrics.Furthermore, the fabrics of the present invention are able to achieve this at lower material costs and relatively low manufacturing complexity as compared to conventional fabrics.

[0071] Edgecomb resistance was high in all samples tested. Despite the strong correlation between fabric RV and seam open area, the inventors did not observe any correlation between fabric RV and edgecomb resistance, indicating that the seam performance improvements described herein are independent of edgecomb resistance. Thus, the present invention provides a novel and unexpected technical contribution to airbag manufacturing.

Claims

1. 1. A woven fabric formed from polyamide fibers, comprising: a. the woven fabric exhibits a fabric relative viscosity (Fabric RV) of 90 or greater; b. the fabric has an edge comb resistance of at least 500 N in each of the warp and weft directions; c. the fabric has a dynamic air permeability of 500 mm / sec or less; A woven fabric, wherein the fabric exhibits improved seam performance upon deployment as compared to a control fabric having the same fabric construction characterized by a fabric RV of greater than 90 as measured by a Hot Air Seam Combing Test, as defined herein.

2. The fabric has a seam open area of ​​≦0.20 mm when measured by the Hot Air Seam Combing Test described herein. 2 / stitch, preferably ≦0.18 mm 2 / stitch, preferably ≦0.16 mm 2 / stitch, preferably ≦0.15 mm 2 / stitch, preferably ≦0.10 mm 2 13. The fabric of claim 1, exhibiting a sewn / stitched weave.

3. 1. A woven fabric formed from polyamide fibers, comprising: a. the woven fabric exhibits a fabric relative viscosity (Fabric RV) of 90 or greater; b. the fabric has an edge comb resistance of at least 500 N in each of the warp and weft directions; c. the fabric has a dynamic air permeability of 500 mm / sec or less; The fabric has a seam open area of ​​≦0.20 mm when measured by the Hot Air Seam Combing Test described herein. 2 / stitch, preferably ≦0.18 mm 2 / stitch, preferably ≦0.16 mm 2 / stitch, preferably ≦0.15 mm 2 / stitch, preferably ≦0.10 mm 2 / Woven fabric exhibiting stitching.

4. 4. The fabric according to any one of the preceding claims, wherein the fabric RV is in the range of 90 to 200, more preferably 90 to 150, more preferably 90 to 130, preferably the fabric RV is at least 100.

5. 5. The fabric according to any one of claims 1 to 4, exhibiting a stiffness in each of the warp and weft directions of 38.0N or less, preferably 35.0N or less, preferably 30.0N or less, preferably 28.0N or less, preferably 25.0N or less.

6. A fabric according to any one of the preceding claims, exhibiting a cloth cover factor of at least 78, preferably at least 85, preferably at least 90, and typically no more than 100.

7. 7. The fabric according to any one of the preceding claims, exhibiting a cloth cover factor of at most 97, preferably at most 95, preferably at most 92, preferably from 78 to 97, preferably from 85 to 97, preferably from 85 to 95, preferably from 85 to 92.

8. The fabric according to any one of the preceding claims, having an edgecomb resistance of at least 600N, preferably at least 700N.

9. The fabric according to any one of claims 1 to 8, wherein the dynamic air permeability is less than or equal to 450 mm / sec.

10. Static air permeability (SAP) is 4.0 or less, preferably 2.5 l / dm 2 The fabric according to any one of claims 1 to 9, wherein the fiber length is 1 / min or less.

11. 11. The fabric of any one of claims 1 to 10, wherein the polyamide is or comprises at least one selected from nylon 6,6 (PA-6,6), nylon 6 (PA-6), nylon 7 (PA-7), nylon 4,6 (PA-4,6), nylon 4,10 (PA-4,10), nylon 5,6 (PA-5,6), nylon 5,10 (PA-5,10), nylon 6,10 (PA-6,10), nylon 12 (PA-12) and nylon 6,12 (PA-6,12).

12. 12. The fabric according to any one of the preceding claims, wherein the polyamide is or comprises PA-6,6.

13. 13. The fabric according to any one of the preceding claims, wherein the fabric exhibits a construction of 16.0 to 22.5 end / cm, preferably 16.0 to 21.0 end / cm.

14. 130~260g / m 2 , preferably 170 to 225 g / m 2 Or 170 to 220 g / m 2 The fabric according to any one of claims 1 to 13, which exhibits a total fabric weight of

15. The fabric according to any one of the preceding claims, exhibiting a total thickness of less than or equal to 0.40 mm, preferably less than or equal to 0.35 mm, preferably between 0.28 and 0.40 mm, preferably between 0.30 and 0.35 mm.

16. 750kg / m 3 Preferably, 725 kg / m or less 3 Typically, 700 kg / m 3 16. The fabric of any one of claims 1 to 15, exhibiting a bulk density of 100% or less and / or wherein the woven fabric has not been calendered or otherwise exposed to high temperatures and pressures.

17. a. the woven fabric exhibits a fabric relative viscosity (Fabric RV) of 90 or greater; b. the fabric has an edge comb resistance of at least 500 N in each of the warp and weft directions; c. the fabric has a dynamic air permeability of 500 mm / sec or less, preferably 450 mm / sec or less; d. the fabric has a stiffness of 38.0 N or less, preferably 35.0 N or less, preferably 30.0 N or less; e. The fabric has a seam open area of ​​≦0.20 mm 2 / stitch, preferably ≦0.18 mm 2 / stitch, preferably ≦0.16 mm 2 / Stitches are shown, f. The fabric preferably has a cloth cover factor of 85-97, preferably 85-95, preferably 85-92, and / or a tensile strength of 170-240 g / m 2 , preferably 170 to 225 g / m 2 , preferably 170 to 220 g / m 2 The total fabric weight is g. The fabric preferably has a strength of 750 kg / m 3 17. The fabric of any one of claims 1 to 16, exhibiting a bulk density of:

18. 18. The fabric of any one of claims 1 to 17, wherein the polyamide is produced from intermediates produced via a biosynthetic or petrochemical pathway.

19. The fabric according to any one of claims 1 to 18, which is a plain weave fabric.

20. The fabric of any one of claims 1 to 19, which is uncoated.

21. The fabric according to any one of the preceding claims, which is coated.

22. The fabric of any one of claims 1 to 21, which is an airbag fabric.

23. An airbag made from the fabric of any one of claims 1 to 22.

24. 24. The airbag of claim 23, which is a frontal, knee, distal or side / thorax airbag, and / or is not a one piece weave (OPW) airbag.

25. 1. A suture formed by twisting together polyamide fibers, wherein fibers extracted from said suture exhibit an RV of 90 or greater.

26. 1. Use of a woven fabric formed from polyamide fibers, comprising: a. the woven fabric exhibits a fabric relative viscosity (Fabric RV) of 90 or greater; b. the fabric has an edge comb resistance of at least 500 N in each of the warp and weft directions; c. the fabric has a dynamic air permeability of 500 mm / sec or less; For airbag fabrics for the purpose of improving the seam performance of the airbag during deployment, preferably the fabric has a seam open area of ​​≦0.20 mm 2 / stitch, preferably ≦0.18 mm 2 / stitch, preferably ≦0.16 mm 2 / stitches and / or said improvement is evaluated in comparison to a control fabric having the same fabric construction and characterized by a fabric RV of greater than 90, and the improvement in seam open area and seam performance is measured by a Hot Air Seam Combing Test as defined herein.

27. 1. A method for improving seam performance in an airbag upon deployment, the method comprising fabricating the airbag from a woven fabric formed from polyamide fibers; a. the woven fabric exhibits a fabric relative viscosity (Fabric RV) of 90 or greater; b. the fabric has an edge comb resistance of at least 500 N in each of the warp and weft directions; c. the fabric has a dynamic air permeability of 500 mm / sec or less; Preferably, the fabric has a seam open area of ​​≦0.20 mm 2 / stitch, preferably ≦0.18 mm 2 / stitch, preferably ≦0.16 mm 2 / stitches and / or the fabric exhibits improved seam performance compared to a control fabric having the same fabric construction and characterized by a fabric RV of greater than 90, the improvement in seam open area and seam performance being measured by a Hot Air Seam Combing Test as defined herein.

28. The use according to claim 26 or the method according to claim 27, wherein the woven fabric is as defined in any one of claims 1 to 22.

Citation Information

Patent Citations

  • Raw yarn for airbag and fabric for airbag

    JP2002266161A

  • High rv filaments and high rv flakes and apparatus and methods for producing filaments thereof

    JP2002529604A

  • Method for producing hollow weave base fabric for air bag

    JP2006299469A

  • Airbag base cloth, airbag base thread, and its preparation process

    JP2009243030A

  • Woven fabric for air bag and method for producing woven fabric for air bag

    JP2009256860A